2007
DOI: 10.1016/j.pscychresns.2006.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Towards a functional topography of sensory gating areas: Invasive P50 recording and electrical stimulation mapping in epilepsy surgery candidates

Abstract: The filtering of sensory information, also referred to as "sensory gating", is impaired in various neuropsychiatric diseases. In the auditory domain, sensory gating is investigated mainly as a response decrease of the auditory evoked potential component P50 from one click to the second in a double click paradigm. In order to relate deficient sensory gating to anatomy, it is essential to identify the cortical structures involved in the generation of P50. However, the exact cerebral topography of P50 gating has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…As in the cognitive inhibition tasks, there is increasingly more evidence to suggest frontal cortex involvement in P50 sensory gating (Grunwald et al, 2003; Korzyukov et al, 2007; Kurthen et al, 2007; Weisser et al, 2001). Both fMRI (Marlow-O’Conner, 2005; Tregellas et al, 2007) and lesion (Knight, Staines, Swick, & Chao, 1999) paradigms have provided evidence for bilateral recruitment of DLPFC in gating.…”
Section: Rationale For Investigating the Relationship Between P50 Gatmentioning
confidence: 99%
“…As in the cognitive inhibition tasks, there is increasingly more evidence to suggest frontal cortex involvement in P50 sensory gating (Grunwald et al, 2003; Korzyukov et al, 2007; Kurthen et al, 2007; Weisser et al, 2001). Both fMRI (Marlow-O’Conner, 2005; Tregellas et al, 2007) and lesion (Knight, Staines, Swick, & Chao, 1999) paradigms have provided evidence for bilateral recruitment of DLPFC in gating.…”
Section: Rationale For Investigating the Relationship Between P50 Gatmentioning
confidence: 99%
“…Kurthen et al analyzing epilepsy surgery candidates on standard therapy with anticonvulsant drug polytherapy, said that the drugs might systematically alter the P50 responses. On the other hand, they did not find any difference in responses comparing patients under complete drug withdrawal and patients under anticonvulsive treatment 22 . It seems unlikely that these medications may affect P50 suppression since no significant differences between the groups of patients with epilepsy were found, although just one of our patients was not taking anticonvulsive drugs.…”
Section: Age Range and Mean Age±standard Deviation (Yearsmentioning
confidence: 79%
“…However, suppression deficit was smaller than that found in individuals with schizophrenia. Few studies have analyzed the P50 auditory evoked potential in patients with epilepsy 14,[21][22][23][24] . One of them has evaluated the double-click paradigm, but it did not study the existence of a suppression deficit 14 .…”
Section: Age Range and Mean Age±standard Deviation (Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this finding, further research is warranted to investigate other candidate brain regions that are known to be functionally impaired in schizophrenia. For example, intrahemispheric gating ratio has been linked to reduced schizophrenia STG cortical thickness (Thoma et al, 2004), and recent depth-electrode research in patients with epilepsy has suggested that medial frontal and sensory-motor cortex are also critical for gating (Kurthen et al, 2007). …”
Section: Discussionmentioning
confidence: 99%